(untitled) - Barnhart, Michael A. (Ithaca, 1987)
Though the subject has been much studied, this book belongs to a small corpus of works based upon both English- and Japanese-language sources. In emphasizing that Japan's drive for empire was rooted in its economic insecurity, the book is in the tradition of James Crowley's Japan's Quest for Autonomy, 1930-38 (1966). Barnhart's work, however, covers a broader time span, is based upon a wealth of documentation that has become available in the past two decades, and also covers U.S.-Japanese diplomatic relations more thoroughly than Crowley's did. Barnhart's book is even-handed and scholarly in tone. Though its appeal will be limited mainly to specialists, general readers who have some knowledge of the topic will find it rewarding
Keywords: National security,Japan,Japan,Japan; Economic conditions,Economic policy,History; 1918-1945,1912-1945; Japan